2014
DOI: 10.1093/ndt/gfu209
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab for minimal-change nephrotic syndrome in adulthood: predictive factors for response, long-term outcomes and tolerance

Abstract: RTX is safe and effective in adult patients with MCNS and could be an alternative to steroids or CNIs in patients with a long history of relapsing MCNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 27 publications
2
53
1
Order By: Relevance
“…22,23 However, persistent remission induced by RTX can be maintained in some patients with INS also after CD19 + recovery. 13,24 This observation suggests a disease-modifying effect of RTX in INS that goes beyond total B cell depletion. A single study showed in vitro a direct effect of RTX on podocyte function.…”
Section: Discussionmentioning
confidence: 94%
“…22,23 However, persistent remission induced by RTX can be maintained in some patients with INS also after CD19 + recovery. 13,24 This observation suggests a disease-modifying effect of RTX in INS that goes beyond total B cell depletion. A single study showed in vitro a direct effect of RTX on podocyte function.…”
Section: Discussionmentioning
confidence: 94%
“…The largest adult cohort of patients with biopsy confirmed that minimal-change glomerulopathy treated with rituximab had a 61% (25/41) complete clinical response with 52% of responders relapsing and had successful re-treatment with rituximab [24]. Similar recent work of 16 adults, one of whom was corticosteroid-resistant, showed full remission in 81% (13/16) of patients with 7 eventually relapsing after 9–28 months with a mean follow-up of 44 months [19].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the mechanism of MCNS is not precisely known, although it is hypothesized that the induction of CD80 in podocytes is triggered by circulating cytokines, microbial products or allergens and is perpetuated by regulatory T cell dysfunction or impaired autoregulatory podocyte functions (2,7). However, recent reports or evidence from clinical practice suggest that rituximab, an anti-CD20 monoclonal antibody, ameliorated the refractory nephrotic syndrome, including frequently relapsing MCNS (8,9). The etiological analysis is difficult because rituximab leads to direct lysis of B cells only, not T cells.…”
Section: Discussionmentioning
confidence: 99%